Activating killer‐cell immunoglobulin‐like receptor haplotype influences clinical outcome following HLA‐matched sibling haematopoietic stem cell transplantation. (20th August 2018) - Heatley, Susan L.; Mullighan, Charles G.; Doherty, Kathleen; Danner, Silke; O'Connor, Geraldine M.; Hahn, Uwe; Szer, Jeff; Schwarer, Anthony; Bradstock, Kenneth; Sullivan, Lucy C.; Bardy, Peter G.; Brooks, Andrew G.
Abstract : Natural killer cells are thought to influence the outcome of haematopoietic stem cell transplant (HSCT), impacting on relapse, overall survival, graft vs host disease (GvHD) and the control of infection, in part through the complex interplay between the large and genetically diverse killer‐cell immunoglobulin‐like receptor (KIR) family and their ligands. This study examined the relationship between KIR gene content and clinical outcomes including the control of opportunistic infections such as cytomegalovirus in the setting of HLA‐matched sibling HSCT in an Australian cohort. The presence of the KIR B haplotype which contain more activating receptors in the donor, in particular centromeric B haplotype genes (Cen‐B), was associated with improved overall survival of patients with acute myeloid leukaemia undergoing sibling HSCT and receiving myeloablative conditioning. Donor Cen‐B haplotype was also associated with reduced acute GvHD grades II to IV whereas donor telomeric‐B haplotype was associated with decreased incidence of CMV reactivation. In contrast, we were not able to show a reduced rate of relapse when the donor had KIR Cen‐B; however, relapse with a donor Cen‐A haplotype was a competing risk factor to poor overall survival. Here, we show that the presence of donor activating KIR led to improved outcome for the patient, potentially through reduced relapse rates and decreased incidence of acute GvHD translating to improved overall survival.